Disgorgement sebagai Upaya Perlindungan Hukum dalam Pengembalian Keuntungan Tidak Sah dan Dana Kompensasi Kerugian Bagi Investor di Bidang Pasar Modal - I Komang Ngurah Wirya Jaya; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2022)
Effects that are included in property can also be interpreted as securities that can cause indirect losses to victims, namely investors, even though they have arrived at the court process. Therefore, to provide legal protection in the return of illegal profits and compensation funds in the capital market, Disgorgement emerged. Not only as an effort to protect, but disgorgement also seeks to provide sanctions to violators of its regulations. In this study, normative law with a statutory approach and a conceptual perspective is used. This study finds that disgorgement can provide protection in the form of return of profits from violators who receive illegal profits or who violate current regulations in the capital market sector. In addition, the legal sanctions given can also provide certainty to violators so that they cannot use and enjoy the illegal profits they get by imposing the transfer or disbursement of their assets contained in financial service institutions.